Religious addiction - Imriné Csákányos, Melinda (Acta Medicinae et Sociologica, 2021)
Talking about religious addiction in today’s age is both a timely and taboo subject. Religion has been a part of human life since ancient times. It is perhaps one of the most exciting and complex areas in research behavioural addictions together with its negative and positive sides. However, when we talk about religious addiction, in addition to the dysfunctional operation of the individual, the dysfunctional operation of the given religious group also appears. I try to explore the topic from several aspects, emphasizing the clarification of the concept and functions of religion, going around its positive and negative effects, and also presenting the methods of its therapeutic nature for young people.